Correlation between the wind speed and the elevation to evaluate the wind potential in the southern region of Ecuador. (September 2021) - Solano, J.C.; Montaño, T.; Maldonado-Correa, J.; Ordóñez, A.; Pesantez, M.
Abstract: In this paper, we use the correlation between the average wind speed and the elevation above sea level to present a regression model for calculating the average wind speed and evaluating the wind potential in the southern region of Ecuador. After obtaining the regression model, an adjustment factor based on the topographic slope has been included, mainly since the wind speed could vary largely as it blows across the lower slope regions or intermediate hills of mountains. Once the wind speed was obtained, both at 10 m and 100 m, the wind power density was calculated, which includes the impact of wind speed and air density. Finally, the model accuracy was obtained by comparing other free access data sources including actual data from meteorological stations, using statistical parameters to quantify the error. According to the results obtained, we find that wind speed has a good correlation with the terrain elevation of the southern region of Ecuador. The simulated wind speed compared to the actual data has errors between 7.75% and 16.89%, which indicates that the model can predict with > 83% accuracy. In addition, both the root means square error and the standard deviations have around 1 m/s of error.